2022
DOI: 10.1021/acs.energyfuels.1c03598
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of an FeS@GQDs Composite for Lithium Storage with Coal Tar Pitch as ″Natural GQDs″

Abstract: Graphene quantum dots (GQDs), a newly emerging zero-dimensional material, have achieved widespread interest in energy storage applications. However, the complicated preparation processes of GQDs involving harsh reagents/conditions, cumbersome purification procedures, or costly precursors hinder their practical use. Herein, we reveal a low-cost and eco-friendly solvothermal method to obtain an FeS@GQDs composite, with coal tar pitch (CTP) as ″natural GQDs″. When evaluated as an anode material in lithium-ion bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Moreover, the small semicircle in the high-frequency region represents the performance dynamics within the electrode material, and activated CMs-650 exhibited a much shorter portion of the Warburg region than activated CMs-700, suggesting better ion diffusion efficiency. These results are consistent with those obtained from the CV curve and constant current charge–discharge tests. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the small semicircle in the high-frequency region represents the performance dynamics within the electrode material, and activated CMs-650 exhibited a much shorter portion of the Warburg region than activated CMs-700, suggesting better ion diffusion efficiency. These results are consistent with those obtained from the CV curve and constant current charge–discharge tests. , …”
Section: Resultssupporting
confidence: 91%
“…These results are consistent with those obtained from the CV curve and constant current charge− discharge tests. 27,28 To further evaluate the electrochemical properties and the cycling performance, as depicted in Figure 10a, a plot of specific capacitance as a function of the cycle number was conducted at a current density of 0.5 A/g for up to 2000 cycles. The loss in specific capacitance based on the maximum value after 2000 cycles was about 3.31%, and the charge/discharge curves can maintain triangular shapes, thus suggesting excellent cycling stability.…”
Section: Surface Area and Porous Volume Of Cmsmentioning
confidence: 99%
“…These prominent electrochemical properties can be ascribed to the successful coupling between FeS and GQDs by forming C-S-C, which provides a large specific surface area and well-developed porosity, leading to improved electrical conductivity and enhanced structural stability. 203 Jiang et al reported a FeS 2 / NPCF composite using C 6 H 5 O 7 (NH 4 ) 3 as carbon source, FeCl 3 as iron source, and NaCl as template. The resulting FeS 2 /NPCF composite showed excellent sodium storage performance with a reversible capacity of 552 mA h g −1 and a capacity retention of 87% after 100 cycles.…”
Section: As Precursormentioning
confidence: 99%
“…Compounding with other materials can alleviate the volume change, enhance the structural stability, reduce the dissolution of active substances, adjust the electronic structure, and improve the conductivity. It is one of the effective strategies to enhance the energy storage dynamics of the electrode and to improve the electrochemical performance. At present, VS 2 -based composites have shown advantages in electrochemical energy storage, such as carbon (e.g., carbon nanotubes, CNTs), , inorganic compounds (e.g., MoS 2 ), and conductive polymers (e.g., PEDOT–PSS, poly­(3,4-ethylenedioxythiophene)-poly­(styrenesulfonate), etc.).…”
Section: Challenges and Solutionsmentioning
confidence: 99%